Equivalent pole concept for tapered power poles - Kalaga, Sriram (Journal of Structural Engineering, 2024)
An Equivalent Pole concept is introduced to analyze tapered power poles. Using stiffness and strength criteria, diameters of equivalent constant section poles are derived for wood and steel poles by comparing deflections and stresses with those of tapered poles. Axial, flexural and torsion loading were considered. The derivations are validated for wood and steel poles using exact computer analyses. Both qualitative and quantitative inferences were drawn and suggestions for further extensions are made.